Electrical Cardioversion in Pregnancy: A Case Report - Rijal, Hima; Thapa, S; Jha, Pooja (Nepal Journal of Obstetrics and Gynaecology, 2022)
A case of 28 years primigravida with refractory tachycardia at term is reported. She was refractory to medical cardioversion. Electrical cardioversion was applied before and after the delivery of baby. With several cycles of variable joules of electrical cardioversion, the normal rhythm was not obtained. However, patient’s rhythm reverted to sinus with anti-arrhythmic medication after third week of cesearean delivery.